Boosting perovskite nanomorphology and charge transport properties via a functional D–π-A organic layer at the absorber/hole transporter interface. Issue 28 (8th July 2020) - Elsenety, Mohamed M.; Stergiou, Anastasios; Sygellou, Labrini; Tagmatarchis, Nikos; Balis, Nikolaos; Falaras, Polycarpos
Abstract : The coating of perovskites with D35 improves the performance of PSCs. D35 plays a versatile functional role. Abstract : The photovoltaic efficiency and stability challenges encountered in perovskite solar cells (PSCs) were addressed by an innovative interface engineering approach involving the utilization of the organic chromophore ( E )-3-(5-(4-(bis(2′, 4′-dibutoxy-[1, 1′-biphenyl]-4-yl)amino)phenyl)thiophen-2-yl)-2-cyanoacrylic acid (D35) as an interlayer between the perovskite absorber and the hole transporter (HTM) of mesoporous PSCs. The organic D–π-A interlayer primarily improves the perovskite's crystallinity and creates a smoother perovskite/HTM interface, while reducing the grain boundary defects and inducing an energy level alignment with the adjacent layers. Champion power conversion efficiencies (PCE) as high as 18.5% were obtained, clearly outperforming the reference devices. Interestingly, the D35-based solar cells present superior stability since they preserved 83% of their initial efficiency after 37 days of storage under dark and open circuit (OC) conditions. The obtained results consolidate the multifunctional role of organic D–π-A molecules as perovskite interface modifiers towards performance enhancement and scale-up fabrication of robust PSCs.